Testing the Semi-Strong Form efficiency to differentiate stock returns between Islamic and Non-Islamic firms: Empirical evidence using dividend announcement from Malaysia. - Saya, Muhammad Mujtuba (2015)
This dissertation conducts an event study in the specific area of Efficient Market Hypothesis (EMH). It concentrates on the semi-strong form and focuses on exploring the impact of dividend announcements on share prices’ of Malaysian stock market (Bursa Malaysia). Further, it commences a comparison of Islamic (Shariah) compliant stocks and non-Islamic compliant stocks. A sample of 60 companies (30 Shariah and 30 Non-Shraiah compliant) were selected from the main board of Bursa Malaysia. An event study was conducted on the recent 3 years with a total of 179 announcements. A T-test was conducted to test the statistical significance of average abnormal returns and cumulative average abnormal returns. The results from the analysis have shown that stock prices react negatively to the dividend announcements. Further it was also found that both; Shariah and non-Shariah data sets were inefficient with regards to the semi-strong form. However overall results suggests that Shariah compliant companies are closer to efficiency when compared to non-Shariah compliant companies.